Performance and Digestibility of Corncob and Cowpea Husk Diets by West African Dwarf Sheep - T.O., Ososanya; Alabi, B.O.; Sorunke, A.O. (Pakistan Journal of Nutrition, 2012)
In the tropics, dry season is characterized by shortage of feeds and staggered growth pattern of ruminants. Corncob (CC) and Cowpea Husk (CH), the by-products of maize and cowpea production respectively may be used as alternative feed resources for ruminants especially during dry season. Therefore, a ten week study was conducted to determine the effects of CC and CH based diets on performance of WAD sheep. In a randomized complete block design, sixteen WAD sheep were allotted to four dietary treatments: A (100% CC), B (66.7% CC + 33.3% CH), C (33.3% CC + 66.7% CH) and D (100% CH). The sheep were allotted to any of the four diets with four animals per treatment. Parameters measured include: dry matter intake, live weight changes, feed conversion ratio and nutrient digestibility. Results showed significant (p<0.05) differences in dry matter intake (22.04 kg in diet A to 41.07 kg in diet C) and LWG (4.14 g/day in diet A to 41.71 g/day in diet C) of sheep across the diets. Also, there were significant (p<0.05) differences in FCR across the diets. The FCR ranged from 14.06 in diet C to 45.68 in diet A. Nutrients digestibility increased with increasing level of cowpea husk in the diets. The DM digestibility value ranged from 65.24% in diet B to 85.04% in diet D. The CP digestibility was also highest in diet D (88.01%) and lowest in diet A (72.06%) while ADF, NDF and ADL were highest in diet C and lowest in diet B. Optimum weight gain and efficient utilization was achieved at 66.7% CH and 33.3% CC inclusion levels.